Subjective Assessment of Pain Level during Phacoemulsification and Extra Capsular Cataract Extraction with Intraocular Lens Implantation under Topical Anesthesia - Awan, Abdul Hamid (Pakistan Journal of Ophthalmology, 2009)
Purpose: To investigate the level of pain in both phacoemulsicification and extra capsular cataract extraction using topical anesthesia with proparacain hydrochloride 0.5% as an alternate to peribulbar and retro bulbar anesthesia. Materials and Methods: Sixty patients undergoing cataract surgery (thirty eyes using phacoemulsicification and thirty eyes with extra capsular cataract extraction technique) were included in the study. All patients received topical anesthesia with proparacain (Alcain) eye drops combined with sponge socked in Alcain eye drops in superior conjuctival sac, which remained there till the end of surgery. In all Phacoemulsification cases incision site was supro-temporal clear corneal for right eyes and supro-nasal clear corneal for left eye with foldable intraocular lenses without sutures. In all cases of extra capsular cataract extraction, clear corneal superior limbal incision was given with implantation of 6.5 mm PMMA intraocular Lens and stitched with shoe-lace continuous 10/0 nylon sutures. All patients were evaluated for intra-operative pain. Subjected pain was assessed by using 4-point scale. Results: 3 patients (10 %) of patients in both groups experienced mild pain during both Phacoemulsification and extra capsular cataract extraction.6 patients (20 %) had moderate pain during passing first suture in extra capsular cataract extraction cases only, for which subconjuctival xylocain was infiltrated just behind incision before suturing. No patient had severe pain during extra capsular cataract extraction in all 30 cases. Conclusion: Topical anesthesia can be safely used not only in Phacoemulsification but also in extra capsular cataract extraction procedure, which is safe and effective alternative to peribulbar and retro bulbar anesthesia, thus, avoiding pain and other complications of regional blocks.